Management of dystocia complicated by fetal ascites in a Holstein Friesian cow - Wasef, Al; Mohanta, Uday Kumar; Hossan, Md Farhad; Islam, Md. Rashedul; Hossain, Hafsa (Ovozoa: Journal of Animal Reproduction, 2025)
A five-and-a-half-year-old crossbred Holstein Friesian cow was presented with a history of prolonged second-stage labor. According to the owner, the first water bag had appeared approximately seven hours prior to reporting to the Upazila Veterinary Hospital in Manoharganj, Cumilla, Bangladesh. Upon on-farm examination, a per-vaginal assessment revealed that the fetus was in a posterior presentation, and the fetal abdomen was markedly distended with fluid, giving it a characteristic "pufferfish-like" appearance. Based on clinical findings, a diagnosis of dystocia due to fetal ascites was established. To relieve the obstruction, a guarded fetotomy knife was used to make an incision in the fetal abdominal wall, allowing evacuation of the excessive peritoneal fluid. Following decompression, the non-viable male fetus was successfully delivered via gentle manual traction. The cow was subsequently treated for five days with antibiotics, non-steroidal anti-inflammatory drugs (NSAIDs), and antihistamines. The post-operative recovery was uneventful, and the cow returned to normal physiological status without complications. This case highlights the clinical importance of timely diagnosis and appropriate intervention in managing dystocia associated with fetal ascites in dairy cattle.